Syntheses, structural diversity and photo-degradation and dye adsorption properties of novel Ni(II)/Co(II) coordination polymers modulated by 4-(4-carboxylphenylmethylthio)benzoic acid ligand. (15th September 2019) - Fan, Chuanbin; Zong, Ziao; Zhang, Xia; Su, Baowei; Zhang, Xiaoyin; Zhu, Zheng; Bi, Caifeng; Fan, Yuhua
Graphical abstract: Two novel 3D functional CPs based on the flexible 4-(4-carboxylphenylmethylthio)benzoic acid ligand have been successively synthesized. Complex2 that is composed of Co(II), 4, 4′-H2 cpmb and 1, 3-Hbib ligand displays good photo-degradation and adsorption properties for the organic dyes. Abstract: Two new coordination polymers (CPs) based on transition metals, namely [Ni2 (4, 4′-cpmb)2 (4, 4′-bbibp)2 (H2 O)4 ] n (1 ) and [Co(4, 4′-Hcpmb)(1, 3-bib)] n (2 ) (flexible 4, 4′-H2 cpmb = 4-(4-carboxylphenylmethylthio)benzoic acid, rigid 4, 4′-bbibp = 4, 4′-bis(benzoimidazo-1-ly)biphenyl and 1, 3-Hbib = 1, 3-bis(1-imidazo-1-ly)benzoic acid), have been designed and successfully synthesized under solvothermal conditions, which have been characterized by elemental analysis, infrared spectra, thermogravimetric (TG) analysis, powder X-ray diffraction (PXRD) and single-crystal X-ray diffraction. Single-crystal X-ray diffraction analysis reveals that1 features a 3D supermolecular structure in ABAB mode by H bonds (O⋯H⋯O) with a 2-fold interpenetratingsql topology framework and2 displays a 3D supermolecular framework by H bonds (O⋯H⋯O) with a rarelyfes topology. Moreover, the photo-degradation and dye adsorption properties of CPs1 –2 have been investigated. Importantly, 2 shows good photo-degradation and dye adsorption properties.